2009
DOI: 10.1088/1742-5468/2009/02/p02005
|View full text |Cite
|
Sign up to set email alerts
|

The Kosterlitz–Thouless transition in thin films: a Monte Carlo study of three-dimensional lattice models

Abstract: We study the phase transition of thin films in the three-dimensional XY universality class. To this end, we perform a Monte Carlo study of the improved two-component φ 4 model, the improved dynamically diluted XY model and the standard XY model on the simple cubic lattice. We study films of a thickness up to L 0 = 32 lattice spacings. In the short direction of the lattice free boundary conditions are employed. Using a finite size scaling (FSS) method, proposed recently, we determine the transition temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(71 citation statements)
references
References 63 publications
(294 reference statements)
6
64
1
Order By: Relevance
“…For Goldstone modes such as spin waves in the XY model the free energy difference arises because standing waves form in the direction perpendicular to the film surface, eliminating modes that can still propagate in the bulk. This gives K G = V k B T ζ(3)/(8πd 3 ), a result well confirmed in computer simulations [7,12,17,18] and analytic calculations [19] for XY spin waves. The experiments in helium did find a difference in film thickness between low temperatures and above T λ similar to but larger than this prediction [9,11]; however a later theory [16] showed that this was primarily due to energy differences in the waves at the free surface of the film and bulk, resulting in a thinning magnitude nearly double the the expression for K G above.We doubt very much that second sound propagates at all in saturated helium films.…”
supporting
confidence: 77%
“…For Goldstone modes such as spin waves in the XY model the free energy difference arises because standing waves form in the direction perpendicular to the film surface, eliminating modes that can still propagate in the bulk. This gives K G = V k B T ζ(3)/(8πd 3 ), a result well confirmed in computer simulations [7,12,17,18] and analytic calculations [19] for XY spin waves. The experiments in helium did find a difference in film thickness between low temperatures and above T λ similar to but larger than this prediction [9,11]; however a later theory [16] showed that this was primarily due to energy differences in the waves at the free surface of the film and bulk, resulting in a thinning magnitude nearly double the the expression for K G above.We doubt very much that second sound propagates at all in saturated helium films.…”
supporting
confidence: 77%
“…However we note that this straightforward approach is subject to systematic errors which get suppressed only logarithmically with increasing L. This makes the accuracy of the numerical or experimental determination of the critical parameters quite problematic. This problem can be overcome by the so-called matching method [56,73,81,86,87,89,90], which allows us to control the whole pattern of the logarithmic corrections, leaving only power-law corrections.…”
Section: B Finite-size Behavior At the Bkt Transitionmentioning
confidence: 99%
“…Since long-range order is rigorously ruled out for finite thickness L at all temperatures T > 0 by the Mermin-Wagner theorem [14,16]; only a rounded L < ∞ transition is possible when T > 0, where the O(2) case is special in that a Kosterlitz-Thouless transition to a low-temperature phase with quasi-long-range order is known to occur at a nonzero temperature T KT (L) < T c (see [38] and its references). The destruction of long-range order at low temperatures caused by low-energy fluctuations is a nonperturbative phenomenon ("nonperturbative mass generation").…”
Section: Introductionmentioning
confidence: 99%